Voices from Chernobyl - Aleksievich, Svetlana, 1948-; Gessen, Keith (Normal : Dalkey Archive Press, 2019)
On April 25, 1986, the worst nuclear reactor accident in history occurred in Chernobyl. Until now, all of the books published in English focused on the facts, names, and data. Voices from Chernobyl presents first-hand accounts of what happened to the people of Belarus and the fear, anger, and uncertainty that they lived through. In order to give a voice to their experiences, Svetlana Alexievich--a journalist by trade--interviewed hundreds of people who had been affected by the meltdown. From innocent citizens to firefighters to those called in to clean up the disaster, Voices from Chernobyl is a crucial document of what happened and how people reacted to it. Alexievich presents these interviews in monologue form, giving readers a harrowing inside view into the minds of the affected people untempered by government spin, accusations, or judgements, leaving the reader with just the life-shattering pain of living through such an event and its aftermath.
Translator's preface -- Historical note -- Prologue: A solitary human voice -- pt. I: The land of the dead : On why we remember ; About what can be talked about with the living and the dead ; About a whole life written down on doors ; By those who returned ; About what radiation looks like ; About a song without words ; About a homeland ; About how a person is only clever and refined in evil ; Soldiers' chorus -- pt. II: The land of the living : About old prophecies ; About a moonlit landscape ; About a man whose tooth was hurting when he saw Christ fall ; About a single bullet ; About how we can't live without Chekhov and Tolstoy ; About war movies ; A scream ; About a new nation ; About writing Chernobyl ; About lies and truths ; People's chorus -- pt. III: Amazed by sadness : About what we didn't know: death can be so beautiful ; About the shovel and the atom ; About taking measurements ; About how the frightening things in life happen quietly and naturally ; About answers ; About memories ; About loving physics ; About expensive salami ; About freedom and the dream of an ordinary death ; About the shadow of death ; About a damaged child ; About political strategy ; By a defender of the Soviet government ; About instructions ; About the limitless power one person can have over another ; About why we love Chernobyl ; Children's chorus ; A solitary human voice -- In place of an epilogue.
"Lannan selections"--Page [241].
"First published in Russian as Tchernobylskaia Molitva by Editions Ostojie, 1997"--Title page verso.
Translation of: Tchernobylskaia molitva.
Nobel Prize Winner, 2015.
107223
Keywords: 1986; Chernobyl Nuclear Accident, Chornobyl, Ukraine, 1986 -- Personal narratives, Belarusian; Chernobyl Nuclear Accident, Chornobyl, Ukraine, 1986 -- Social aspects -- Belarus; Chernobyl Nuclear Accident, Chornobyl, Ukraine, 1986 -- Environmental aspects -- Belarus; Social aspects; Nobel Prize for Literature laureate -- 2015; Chernobyl Nuclear Accident; Radiation Injuries; History, 20th Century; Radioactive Fallout -- adverse effects; Radioactive Hazard Release; Survivors; Ukraine -- Chornobyl; Republic of Belarus; Personal narratives -- Belarusian; Interview